LABORATORY AND INSTRUMENTAL APPROACHES TO DIAGNOSTICS OF NON-ALCOHOLIC FATTY LIVER DISEASE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease with a metabolic pathogenesis, the prevalence of which is increasing worldwide. In some patients, the disease may progress to severe forms of liver disease, such as fibrosis and cirrhosis, which are associated with the risk of death. NAFLD is expected to become one of the leading causes of liver transplantation in the coming years. [1,3] The increase in the prevalence of the disease is associated with the growing epidemic of obesity and type 2 diabetes.[2] The pathogenesis of non-alcoholic fatty liver disease (NAFLD) is based on insulin resistance and hyperinsulinemia, which lead to significant disturbances in lipid and carbohydrate metabolism, as well as to an imbalance between the intake and utilization of fats. As a rule, NAFLD is asymptomatic and is detected accidentally during examination of patients seeking medical care for arterial hypertension, coronary heart disease, peripheral vascular pathologies, obesity, or type 2 diabetes.